2013
DOI: 10.1016/j.cub.2013.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Numb Inhibits the Recycling of Sanpodo in Drosophila Sensory Organ Precursor

Abstract: In metazoans, unequal partitioning of the cell-fate determinant Numb underlies the generation of distinct cell fates following asymmetric cell division [1-5]. In Drosophila, during asymmetric division of the sensory organ precursor (SOP) cell, Numb is unequally inherited by the pIIb daughter cell, where it antagonizes Notch [1, 6-8]. Numb inhibits Notch partly through inhibiting the plasma membrane localization of Sanpodo (Spdo), a transmembrane protein required for Notch signaling during asymmetric cell divis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
81
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(86 citation statements)
references
References 35 publications
(63 reference statements)
5
81
0
Order By: Relevance
“…A recent study suggested that Numb suppresses Notch activity either by facilitating lysosomal degradation of Notch or by reducing its recycling to the plasma membrane [23]. Numb also antagonizes the Notch pathway via facilitating the endocytosis of Drosophila sanpodo, which is a membrane protein that is required for Notch activation [24]. These findings suggest that Numb suppresses Notch activity by regulating endosomal trafficking.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…A recent study suggested that Numb suppresses Notch activity either by facilitating lysosomal degradation of Notch or by reducing its recycling to the plasma membrane [23]. Numb also antagonizes the Notch pathway via facilitating the endocytosis of Drosophila sanpodo, which is a membrane protein that is required for Notch activation [24]. These findings suggest that Numb suppresses Notch activity by regulating endosomal trafficking.…”
Section: Introductionmentioning
confidence: 67%
“…Numb carries out these functions via regulating endocytic trafficking of several key molecules, such as Notch, sanpodo, cadherins and integrins [4,7,9,14,17,18,23,24,26,51,52]. Although in all these contexts Numb functions as an endocytic adaptor protein, the exact role of Numb in endocytic trafficking remains an open question.…”
Section: Discussionmentioning
confidence: 99%
“…The cell fate determinant Neuralized, which is unequally inherited by the pIIb cell at cytokinesis (Le Borgne and Schweisguth, 2003), promotes the basal-to-apical transcytosis of Delta in epithelial cells (Benhra et al, 2010). Furthermore, the new adherens junctions at the apical side have also been proposed to act as a platform for Notch signalling during cytokinesis because Notch accumulates there in SOPs that have been depleted of the clathrin adaptor complex AP-1, and loss of AP-1 results in Notch gain of function (Benhra et al, 2011;Cotton et al, 2013). These data raise the possibility that Notch can also be activated at the apical interface above the midbody (Fig.…”
Section: Cell-cell Signalling At the New Membrane Interfacementioning
confidence: 99%
“…SOPs divide asymmetrically along the antero-posterior axis to produce an anterior pIIb cell and a posterior pIIa cell (Gho and Schweisguth, 1998;Schweisguth et al, 1996). Cell fate acquisition relies on the differential activation of the transmembrane receptor Notch through its ligand Delta; Notch is activated in the pIIa cell and inhibited in the pIIb cell by Numb, which, in turn, is unequally inherited by this cell during mitosis (Cotton et al, 2013;Couturier et al, 2013;Couturier et al, 2012;Frise et al, 1996;Guo et al, 1996;Rhyu et al, 1994). Furthermore, Notch and Delta are internalized into a subset of multivesicular endosomes, marked with Smad anchor for receptor activation (Sara), which unequally partitions into the pIIa cell during cytokinesis (Coumailleau et al, 2009).…”
Section: Cell-cell Signalling At the New Membrane Interfacementioning
confidence: 99%
“…Notch is constantly endocytosed (McGill et al, 2009), and the signaling outcome arising from this internalized pool of Notch is carefully controlled by several factors. On the one hand, the protein Numb is a conserved inhibitor of the pathway that acts at this level (Cotton et al, 2013;Couturier et al, 2013Couturier et al, , 2014Reichardt and Knoblich, 2013). This factor interacts with components of the AP-2 complex and prevents endosome-to-plasma membrane recycling of Notch; in addition, Numb also promotes the lysosomal degradation of the receptor (McGill et al, 2009).…”
Section: Discussionmentioning
confidence: 99%